2016
DOI: 10.1007/s00256-016-2480-x
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo quantitative multiparametric MRI mapping of human meniscus degeneration

Abstract: QMRI mapping holds promise in the objective evaluation of human meniscus. Although sufficient discriminatory power of T1, T1ρ, T2, and UTE-T2* was only demonstrated for the histological extremes, these data may aid in the future MRI-based parameterization and quantification of human meniscus degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 39 publications
2
44
0
Order By: Relevance
“…After importing the MR raw data and time constants of each pixel into Matlab R2015a software (Matlab, Natick, MA, USA), spatially resolved quantitative T1r maps were generated of the mid-sagittal image using predefined monoexponential fitting routines 12,25,30 . R 2 statistics was used to check fit quality.…”
Section: Mri Data Analysismentioning
confidence: 99%
“…After importing the MR raw data and time constants of each pixel into Matlab R2015a software (Matlab, Natick, MA, USA), spatially resolved quantitative T1r maps were generated of the mid-sagittal image using predefined monoexponential fitting routines 12,25,30 . R 2 statistics was used to check fit quality.…”
Section: Mri Data Analysismentioning
confidence: 99%
“…In healthy subjects at the unloaded situation, inner lateral and medial posterior horn values were higher than in the outer zone, suggesting underlying differences in macromolecular organization in these subregions of the meniscus. Similarly, Nebelung et al 36 investigated an ex vivo quantitative multiparametric MRI mapping study of degenerated human menisci that showed T 1 , T 1ρ , T 2 , and UTE-T 2 * relaxation times are functionally related to histological meniscus degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Overall qDESS T 2 and MOAKS scores for cartilage, stratified by degree of OA, are summarized in Table 4. [7,16,29]). Differences in qDESS T 2 values were statistically significant between the three subject groups (p < 0.01; Fig.…”
Section: Reproducibility Of Klg Scoringmentioning
confidence: 99%